The Dual Role of Women in Increasing Family Income (Study in Indrapuri District, Aceh Besar Regency) - Vilzati, Vilzati; Roza, Teuku Andi; Marlina, Leni; Nurrahmad, Nurrahmad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
The involvement of women in the economic sector, especially in the agricultural sector, aims to improve the welfare of their family members. With the active role of women in economic activities in Indrapuri District, Aceh Besar Regency has implications for increasing family income. The aim of this research is to find out and describe the role of women and supporting factors in increasing family income in Indrapuri District, Aceh Besar Regency. This study uses a qualitative approach method. The conclusion of the study shows that with the role of womenIndrapuri DistrictAceh Besar Regency in increasing family income both in the economic and agricultural sectors has been running well and smoothly and the benefits have been felt by families, however the role of women has not been able to change the poverty rate, because the income obtained is only enough to be used for consumption alone. Meanwhile, related to supporting factors for the role of women in increasing family income in Indrapuri District, Aceh Besar Regency consists of one's own will and permission from the husband in carrying out one's role.